Randomized Trial of Near-infrared Incisionless Fluorescent Cholangiography. Issue 6 (December 2019) - Dip, Fernando; LoMenzo, Emanuelle; Sarotto, Luis; Phillips, Edward; Todeschini, Hernan; Nahmod, Mario; Alle, Lisandro; Schneider, Sylke; Kaja, Ludwig; Boni, Luigi; Ferraina, Pedro; Carus, Thomas; et al.
Abstract : Background: Incisionless near-infrared fluorescent cholangiography (NIFC) is emerging as a promising tool to enhance the visualization of extrahepatic biliary structures during laparoscopic cholecystectomies. Methods: We conducted a single-blind, randomized, 2-arm trial comparing the efficacy of NIFC (n = 321) versus white light (WL) alone (n = 318) during laparoscopic cholecystectomy. Using the KARL STORZ Image1 S imaging system with OPAL1 technology for NIR/ICG imaging, we evaluated the detection rate for 7 biliary structures—cystic duct (CD), right hepatic duct (RHD), common hepatic duct, common bile duct, cystic common bile duct junction, cystic gallbladder junction (CGJ), and accessory ducts —before and after surgical dissection. Secondary calculations included multivariable analysis for predictors of structure visualization and comparing intergroup biliary duct injury rates. Results: Predissection detection rates were significantly superior in the NIFC group for all 7 biliary structures, ranging from 9.1% versus 2.9% to 66.6% versus 36.6% for the RHD and CD, respectively, with odds ratios ranging from 2.3 (95% CI 1.6–3.2) for the CGJ to 3.6 (1.6–9.3) for the RHD. After dissection, similar intergroup differences were observed for all structures except CD and CGJ, for which no differences were observed. Significant odds ratios ranged from 2.4 (1.7–3.5) for the common hepatic duct to 3.3 (1.3–10.4) for accessory ducts. Increased body mass index was associated with reduced detection of most structures in both groups, especially before dissection. Only 2 patients, both in the WL group, sustained a biliary duct injury. Conclusions: In a randomized controlled trial, NIFC was statistically superior to WL alone visualizing extrahepatic biliary structures during laparoscopic cholecystectomy. Registration number: NCT02702843